Manajerial Bagi UMKM Produktif di Kota Lubuklinggau - Hendra Hadiwijaya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2023)
The purpose of this Community Service focus is on Managerial Training for Productive Micro, Small and Medium Enterprises (MSMEs) in Lubuklinggau City, namely to provide understanding to MSME actors about Managerial. This training activity was held at the Dewinda Hotel, Lubuk Linggau City, which took place from 6 to 8 October 2021. The training method used was to use a logic model for evaluation and socialization by providing managerial material for Productive MSMEs and participants were given the opportunity to asked about MSME management through four components, namely input, process, output, and outcomes. In addition to using technical analysis of Structural Equation Modeling (SEM) with the Variance or Component Based (VB-SEM) approach with the Partial Least Squares (PLS) technique to examine the effect of managerial training on motivation and its implications for the Spirit of Leadership for MSME actors in Lubuk Linggau City, with the sample used as many as 42 respondents. Community service can reduce the negative impact caused by a lack of managerial knowledge or limited experience from MSME actors. So that the results of this training can improve and improve the Quality of Human Resources (HR) of MSME actors, and be able to set more realistic business goals, besides that proper business management can create a comfortable atmosphere, improve time discipline, expedite all activities and in the end can increase business turnover.